Dialectic in Sociology - Schneider, Louis (American Sociological Review, 1971)
and process: Cross-level hypotheses. Behavioral Science 10:197-237, 337-379, 380411. Nisbet, R. A. 1970 Developmentalism, a critical approach. In J. C. McKinney and E. A. Tiryakian (eds.), Theoretical Sociology. New York: Appleton-Century-Crofts. Odum, H. 1936 Southern Regions of the United States. Chapel Hill: University of North Carolina Press Quarton, G. C., T. Melnechuk, and F. O., Schmitt 1967 Neurosciences. New York: Rockefeller University Press. Rapoport, A. 1968 philosophical view. In J. H. Milsum (ed.), Positive Feedback. Oxford: Pergamon. Richardson, L. F. 1960 Arms and Insecurity: A Mathematical Study of the Causes and Origins of War. Nicolas Rashevsky and Ernesto Trucco (ed.). Pittsburgh: Boxwood Press. Shapiro, D. and A. Crider 1969 Psychophysiological approaches in social psychology. Pp. 1-49 in G. Lindzey and E. Aronson (eds.), Handbook of Social Psychology, Vol. III., 2nd Edition. Reading, Massachusetts: Addison-Wesley. Watzlawick, P., J. H. Beavin, and D. D. Jackson 1967 Pragmatics of Human Communication. New York: Norton. Winsborough, H. H. 1965 The changing regional character of the South. In John C. McKinney and E. T. Thompson, South in Continuity and Change. Durham, N.C.: Duke University Press.